Stres akademik : faktor risiko dan dampaknya terhadap kesehatan mental mahasiswa - Arifah, Elvi Nisaul (Maliki Interdisciplinary Journal, 2026)
Academic stress has become an increasingly relevant issue in higher education as academic demands and the complexity of students’ learning environments continue to intensify. Pressure arising from academic workload, evaluation systems, and social expectations can negatively affect students’ psychological well-being when not managed adaptively. This article aims to examine academic stress as a risk factor affecting students’ mental health through a theoretical and empirical perspective. The discussion focuses on the characteristics of academic stress, internal and external risk factors influencing its occurrence, and its implications for students’ psychological conditions. The analysis indicates that academic stress is shaped by the interaction between personal factors, such as emotional regulation, learning motivation, and academic self-efficacy, and environmental factors, including learning systems, interpersonal relationships, and social pressure. Prolonged academic stress contributes to increased anxiety, depressive symptoms, academic burnout, and a decline in overall mental well-being among students. Therefore, managing academic stress requires a comprehensive approach that strengthens individual coping capacities while fostering a more supportive academic environment. A deeper understanding of academic stress is expected to serve as a foundation for developing preventive strategies and interventions aimed at promoting sustainable mental health among university students.